THE ROLE OF NCT DREAM AS BRAND AMBASSADOR IN BUILDING BRAND AWARENESS LEMONILO’S INSTAN NOODLE: (Case Study On Lemonilo’s Instagram Account) - Azizah, Aini; Damastuti, Riski (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2023)
The rise of the use of Korean artists as brand ambassadors is a separate phenomenon. Many of the local companies are taking advantage of the excited moment of the Korean fever that is currently happening to Indonesian society. The use of brand ambassadors is one of a company's marketing communication strategies in attracting the attention of the audience. The use of Korean artists as brand ambassadors will influence consumers to remember a brand and a good reputation as well as a broad fan base will build brand awareness. Based on this phenomenon, researchers want to examine the role of NCT Dream as a brand ambassador in building brand awareness of Lemonilo instant noodles. This research was compiled using a qualitative research method with descriptive analysis, which will describe the facts quoted systematically and using the case study method. The results of this study state that NCT Dream's involvement as the brand ambassador for Lemonilo instant noodles has been successful in attracting the attention of a wider audience, especially NCT Dream fans or K-popers and building brand awareness of Lemonilo instant noodles. Keywords: Brand Ambassador; NCT Dream; Brand Awareness